ChemInform Abstract: Catalytic Enantioselective Synthesis of Tertiary Thiols from 5H‐Thiazol‐4‐ones and Nitroolefins: Bifunctional Ureidopeptide‐Based Broensted Base Catalysis. Issue 13 (1st April 2014) - Diosdado, Saioa; Etxabe, Julen; Izquierdo, Joseba; Landa, Aitor; Mielgo, Antonia; Olaizola, Iurre; Lopez, Rosa; Palomo, Claudio
Abstract The first catalytic Michael addition reaction of α‐mercapto carboxylate surrogates with nitroolefins is developed to synthesize chiral 5H‐thiazol‐4‐ones having a quaternary carbon center.